An investigation of the relationship between branchless banking activities and profitability of commercial banks in Zimbabwe: Panel Data Analysis (2011 – 2017) - Nyimai, Ernest (Midlands State University, 2019)
The motive behind carrying out of this study was the ever changing and unstable profitability levels experienced in the Zimbabwe banking sector particularly after the adoption of various branchless banking activities by various commercial banks. The purpose of this study was to investigate the relationship between the branchless banking activities and profitability of banks using a case study of commercial banks in Zimbabwe. Various theories and empirics were reviewed and have revealed that some branchless banking activities has positive relationship with profitability of commercial banks whilst others are inversely related to profits. The findings on the literature reviewed have somehow differed in the forms of branchless banking activities that were found significant in explaining bank profits. The research used micro panel annual data for 12 commercial banks for a period of 7 years (2011-2017). Diagnostic tests were performed on the data prior to estimations of the Pooled OLS regression. Return on Assets was used as a measure of bank profits. The study found that mobile banking, debit cards, RTGS and POS were statistically significant in determining bank profits. However, POS was found to be inversely related to bank profits. The researcher then concluded that mobile banking, debit cards, RTGS and POS are the major forms of branchless banking adopted by banks in Zimbabwe. Recommendations were that among others, banks must shift from traditional to branchless banking activities, increase awareness on the activities and increasing investment in branchless banking activities. Use of different methodology and case studies for further research study on the similar topic was recommended.